Potential Phosphorylation of Viral Nonstructural Protein 1 in Dengue Virus Infection - Thanyaporn Dechtawewat; Sittiruk Roytrakul; Yodying Yingchutrakul; Sawanya Charoenlappanit; Bunpote Siridechadilok; Thawornchai Limjindaporn; Arunothai Mangkang; Tanapan Prommool; Chunya Puttikhunt; Pucharee Songprakhon; Kessiri Kongmanas; Nuttapong Kaewjew; et al. (Viruses, 2021)
Dengue virus (DENV) infection causes a spectrum of dengue diseases that have unclear underlying mechanisms. Nonstructural protein 1 (NS1) is a multifunctional protein of DENV that is involved in DENV infection and dengue pathogenesis. This study investigated the potential post-translational modification of DENV NS1 by phosphorylation following DENV infection. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), 24 potential phosphorylation sites were identified in both cell-associated and extracellular NS1 proteins from three different cell lines infected with DENV. Cell-free kinase assays also demonstrated kinase activity in purified preparations of DENV NS1 proteins. Further studies were conducted to determine the roles of specific phosphorylation sites on NS1 proteins by site-directed mutagenesis with alanine substitution. The T27A and Y32A mutations had a deleterious effect on DENV infectivity. The T29A, T230A, and S233A mutations significantly decreased the production of infectious DENV but did not affect relative levels of intracellular DENV NS1 expression or NS1 secretion. Only the T230A mutation led to a significant reduction of detectable DENV NS1 dimers in virus-infected cells; however, none of the mutations interfered with DENV NS1 oligomeric formation. These findings highlight the importance of DENV NS1 phosphorylation that may pave the way for future target-specific antiviral drug design.